Implementasi Pembelajaran Tematik di Sekolah Dasar - Ejen Jenal Mutaqin; Lutfi Asyari; Neni Nadiroti Muslihah; Widdy Sukma Nugraha (Jurnal Pekemas, 2020)
This community service aims to provide insight into knowledge about the implementation of thematic learning in the Elementary School Wanaraja Garut District, by providing knowledge about the management of learning problems with professional development to increase professionalism for educators in elementary schools. Basic problems in three stages of preparation, implementation and evaluation activities. The results of community service activities show a level that shows an indication of the similarity in the mindset of participant, a positive response from community service participants related to the implementation of thematic learning in elementary schools